Oxypeucedanin is a Mechanism-based Inactivator of CYP2B6 and CYP2D6 - Zhang, Kehan; Li, Yilin; Fu, Yao; Cui, Tiantian; Wang, Qian; Mao, Xu; Peng, Ying; Zheng, Jiang (Current Drug Metabolism, 2021)
Background: Herbal medicine Angelica dahurica is widely employed for the treatment of rheumatism and pain relief in China. Oxypeucedanin is a major component in the herb. Objectives: The objectives of this study are aimed at the investigation of mechanism-based inactivation of CYP2B6 and CYP2D6 by oxypeucedanin, characterization of the reactive metabolites associated with the enzyme inactivation, and identification of the P450s participating in the bioactivation of oxypeucedanin. Methods: Oxypeucedanin was incubated with liver microsomes or recombinant CYPs2B6 and 2D6 under designed conditions, and the enzyme activities were measured by monitoring the generation of the corresponding products. The resulting reactive intermediates were trapped with GSH and analyzed by LC-MS/MS. Results: Microsomal incubation with oxypeucedanin induced a time-, concentration-, and NADPH-dependent inhibition of CYPs2B6 and 2D6 with kinetic values of KI/kinact 1.82 μM/0.07 min-1 (CYP2B6) and 8.47 μM/0.044 min-1 (CYP2D6), respectively. Ticlopidine and quinidine attenuated the observed time-dependent enzyme inhibitions. An epoxide and/or γ-ketoenal intermediate(s) derived from oxypeucedanin was/were trapped in microsomal incubations. CYP3A4 was the primary enzyme involved in the bioactivation of oxypeucedanin. Conclusion: Oxypeucedanin was a mechanism-based inactivator of CYP2B6 and CYP2D6. An epoxide and/or γ- ketoenal intermediate(s) may be responsible for the inactivation of the two enzymes.
Keywords: bioactivation